1990
DOI: 10.1093/jaoac/73.4.605
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Composition. Part 1. Limitations of FTC Method When Applied to Cigarettes That Heat Instead of Burn Tobacco

Abstract: The design of a new cigarette that heats rather than burns tobacco calls for modifications to the Federal Trade Commission (FTC) method for analytical smoking. These changes Include eliminating sample conditioning at 75 °F and 60% RH, exercising greater care In lighting cigarettes, and smoking cigarettes to self-extinguishment rather than to a predetermined butt length as a measure of complete consumption. By several gross analytical measures, smoke condensate from the new cigarette differs substantially from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Under standardized smoking conditions (52), Premier delivered a MS with low levels of most of the toxic and genotoxic agents compared to concentrations of these agents in the MS of the University of Kentucky reference filter cigarette. Short-term bioassays indicated that the MS of Premier most likely exhibits reduced toxic and genotoxic activities (125)(126)(127)(128)(129). In 1988, Premier was placed on a test market; however, it was not accepted by the consumers.…”
Section: G New Types Of Cigarettesmentioning
confidence: 99%
See 2 more Smart Citations
“…Under standardized smoking conditions (52), Premier delivered a MS with low levels of most of the toxic and genotoxic agents compared to concentrations of these agents in the MS of the University of Kentucky reference filter cigarette. Short-term bioassays indicated that the MS of Premier most likely exhibits reduced toxic and genotoxic activities (125)(126)(127)(128)(129). In 1988, Premier was placed on a test market; however, it was not accepted by the consumers.…”
Section: G New Types Of Cigarettesmentioning
confidence: 99%
“…The tar consists of 33% water, 47% glycerol, and 17% of various other compounds. The emissions of the major smoke carcinogens, such as BaP, 2-naphthylamine, 4-aminobiphenyl, and the TSNA, are lowered by 85-95% (126)(127)(128)(129). The particulate matter of the aerosol generated by smoking Eclipse, according to the FTC standard method, contains as major a constituent about 47% glycerol (in the low-yielding Eclipse this means 2.4 mg glycerol in 5.1 mg smoke particulates) (129).…”
Section: G New Types Of Cigarettesmentioning
confidence: 99%
See 1 more Smart Citation